2019
DOI: 10.3390/w11122576
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Analysis of Operating Conditions of a Circular Flap Gate for an Automatic Upstream Water Level Control

Abstract: This article introduces a flow controller for an upstream water head designed for pipe culverts used in drainage ditches or wells. The regulator is applicable to water flow rates in the range of Qmin < Q < Qmax and the water depth H0, exceeding which causes the gate to open. Qmin flow denotes the minimum flow rate that allows water to accumulate upstream of the controller. Above the maximum flow rate Qmax, the gate remains in the open position. In the present study, the position of the regulator’s gate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Changing the position of the Magnet, bringing it closer to the lid, leads to an increase in the closing moment of the lid, which leads to an increase in the water level at which the lid H0 opens, and a minimum flow of Qmin. such problems are considered [12]. According to the dynamic collision of watercourses, a model with a swing of mazels was created, to reduce the size of the modeling zone and the estimated time during modeling, two general types of bridge supports were considered, the research results showed engineers that the water flow velocity and pressure around the bridge support were considered, and the technique proposed in the article significantly increased the accuracy of the calculated force values [13].…”
Section: Introductionmentioning
confidence: 99%
“…Changing the position of the Magnet, bringing it closer to the lid, leads to an increase in the closing moment of the lid, which leads to an increase in the water level at which the lid H0 opens, and a minimum flow of Qmin. such problems are considered [12]. According to the dynamic collision of watercourses, a model with a swing of mazels was created, to reduce the size of the modeling zone and the estimated time during modeling, two general types of bridge supports were considered, the research results showed engineers that the water flow velocity and pressure around the bridge support were considered, and the technique proposed in the article significantly increased the accuracy of the calculated force values [13].…”
Section: Introductionmentioning
confidence: 99%
“…Automatic movable gates are installed in the inlet heads of culverts and drainage pipes [4]. In irrigation, hydro-automatic gates are used, which include the Begeman gate [5] (or flap gate) and the Romaine gate, operating under free flow conditions [6].…”
Section: Introductionmentioning
confidence: 99%